(untitled) (Annals of Medical Research, 2023)
Aim: The aim of this study is to assess the effect of fasting on the ultrastructure and vascular density of the optic disc and macula by optical coherence tomography angiography (OCT-A). Materials and Methods: 38 eyes of 19 healthy subjects were enrolled in this study. AngioVue OCT-A images of optic disc and macula were taken during fasting and non-fasting periods. Retinal nerve fiber layer (RNFL) thickness, radial peripapillary capillary vessel density (VD), central macular thickness (CMT), macular superficial, deep and choroid capillary plexus VD, foveal avascular zone (FAZ), acircularity index of foveal avascular (AI), foveal density (FD) zone were compared. Results: No statistically significant difference was found between the two periods in terms of RNFL thickness, radial peripapillary capillary VD. Parafoveal superficial macular VD was significantly reduced in fasting period than non-fasting period (46.21% ± 5.71% & 48.15% ± 4.45% p= 0.039). Whole image, parafoveal and perifoveal total retinal VD was significantly decreased in fasting period than non-fasting period (49.46% ± 4.28% & 50.88% ± 3.43% p=0.029; 52.38% ± 5.85% &54.60% ± 3.74% p= 0.012; 49.99% ± 4.58% & 51.35% ± 3.40% p= 0.030 ). CMT, deep retinal VD, choriocapillary VD, FAZ area, FAZ perimetry, AI, FD and nonflow area were not statistically different in fasting and non-fasting periods (p > 0.05) Conclusion: Fasting during Ramadan causes alterations in retinal microcirculation.